Analisis Pengelolaan Perusahaan Daerah Isen Mulang Kota Palangka Raya - Masrukin Masrukin; Danang Ristiantoro (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
The purpose of this research is to know and describe the management of the District company Isen Mulang City Palangka Raya In this regard with good corporate governance principles. The type of research used in this study is descriptive using a qualified research method. The type of data in this study is primary data and secondary data that includes the board of directors, supervisory board and employees in the regional area of Isen Mulang City Palangka Raya. While its secondary data is emerging from Perda about the establishment and financial report of the regional company Isen Mulang City Palangka Raya, other data sources, data collection techniques using interviews, observation, and documentation. Based on the results of this research the management of the District company Isen Mulang Kota Palangka Raya based on good corporate governance principle has not been done with the maximum this can be seen from the not yet implemented Openness is still the absence of accessible websites or blogs, not yet the clarity of the details of tasks, and internal control of the company, suitability has not carried out well the company has not committed social responsibility, not yet Contribution to the PAD, has not paid the income tax because the company has not acquired profit, independence or independent has not carried out well-characterized by the still the responsibility of the responsibilities among employees, Fairness has not been implemented with the maximum that is characterized by the dissemination of information about the recruitment of employees has not been widely and still with a family system and not yet carried out training and development of employees.